2006
DOI: 10.1111/j.1463-1326.2006.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Do low levels of circulating adiponectin represent a biomarker or just another risk factor for the metabolic syndrome?

Abstract: The metabolic syndrome is currently defined by various combinations of insulin resistance, obesity, dyslipidaemia and hypertension. The tendency for these risk factors to appear simultaneously suggests a single aetiologic basis. A low level of circulating adiponectin is associated with the appearance of each metabolic syndrome risk factor. The following review summarizes a large body of evidence that suggests a low level of circulating adiponectin represents an independent risk factor and a possible biomarker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 201 publications
(239 reference statements)
3
36
0
2
Order By: Relevance
“…2 These characteristics have been reported in a previous publication ( 14 ). 3 Analysis was performed on transformed values.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…2 These characteristics have been reported in a previous publication ( 14 ). 3 Analysis was performed on transformed values.…”
supporting
confidence: 83%
“…Of these adipose tissue-derived hormones, adiponectin and leptin have attracted much interest because of their significant impact on cardiovascular health. Adiponectin is known as having anti-inflammatory, antiatherogenic and insulin-sensitizing properties 1 and it has been previously demonstrated that a low concentration of this hormone is an independent predictor of the metabolic syndrome 2 , coronary heart disease 3 and type 2 diabetes 4 . In the case of leptin, mixed results have been obtained, some studies observed that a high leptin concentration is a predictor of coronary events and type 2 diabetes independently of adiposity 5,6 while others showed that the association between leptin concentrations and these major chronic diseases is largely explained by concomitant variations in body weight or BMI 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our data indicate that in this 'lean range', the amount of SAT may be an important determinant of several metabolic cardiovascular risk factors, such as higher TG and lower high-density lipoprotein -cholesterol concentrations. Adiponectin, as a marker of metabolic syndrome, 40 and leptin, as an indicator of the amount of adipose tissue mass, 41 have been associated with insulin resistance and HT. 42 Patel et al 43 found inverse association of adiponectin with insulin resistance, visceral adiposity, and positive family history of coronary heart disease, HT and type 2 diabetes in young adults.…”
mentioning
confidence: 99%
“…Adipose tissue is a rich source of metabolically active molecules, including adiponectin and leptin (4). Adiponectin is considered a marker of metabolic syndrome (5), and leptin directly reflects the amount of adipose tissue mass (6). Obesity is also strongly associated with high-sensitivity C-reactive protein (hs-CRP), a marker of chronic systemic inflammation (7).…”
Section: Introductionmentioning
confidence: 99%